Gender Stereotyping in Brown Watson’s Picture Books (2012) - Intan Purnama Sari; Christy Tisnawijaya (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
This paper discusses gender stereotyping represented in two selected picture books, My Little Book of Stories for Girls and My Little Book of Stories for Boys by Brown Watson (2012). The verbal and visual texts were examined to reveal the symbolical meanings of gender stereotyping which then argued by using Judith Butler’s gender performativity. The analysis results in a clear distinction between the performances of female and male characters. By separating female and male characters into completely different categorizations through their appearances, traits, and behavior, the first picture book represents feminine gender stereotypes that females are princesses who stay in the palace while the second represents masculine gender stereotypes that males are outdoor working individuals.